A rend világa. Tudásalapú Európa? Kutatás-fejlesztés-innováció és a gyakorlati hasznosítás rögös viszonya, célszerű jövője a rendszerelmélet és a rendszerszemlélet tükrében - Ziegler, Éva (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Our aim is to provide a correct answer to the European challenges. To this end, we use the common base of all kinds of good approaches, the one which is less widespread but very fruitful and . system theoretical approach. We analyze Europe as a system, how it is related to its system parts and to the environmental gross-system. We identify how and why to place the concept 'challenge' in the frame of the theory, in the circles of physical effects controlling multiple complex and hierarchical systems. We draw the conclusion which kind of system and related model allows us to achieve our target, to get us correct answers. Finally, we list the main groups of necessary priority tasks, in order to let the system operate as a result and we record its resource conditions.